Paleocene/Eocene carbon feedbacks triggered by volcanic activity - Sev Kender (Nature Portfolio, 2021)
The Paleocene–Eocene boundary coincided with runaway global warming possibly analogous to future climate change, but the sources of greenhouse gasses have remained unresolved. Here, the authors reveal volcanism triggered initial warming, and subsequent carbon was released after crossing a tipping point.